Nanomineral fortification on traditional Saddah Gohoge grits - Husain , Rahim; Djailani , Fernandy; Harmain , Rita Marsuci (Food Science and Technology, 2023)
Saddah Gohoge grits is a traditional food in Gorontalo Province, Indonesia, especially the elderly and when children are growing. The study aimed to obtain the physical, chemical, and organoleptic characteristics of the Saddah Gohoge grits fortification of nanomineral fish bones from the family Lutjanus sp. The materials used were Saddah Gohoge corn, bone nanominerals of the family Lutjanus sp. The nanomineral using precipitation method. The proximate, viscosity, and colour using Association of Official Analytical Chemists (2005), and organoleptic using non-parametric. Data analysis using analysis of variance, descriptive and kruskal wallis. Proximate levels increased along with the increase in the concentration of fortified nanomineral fish bones of the Lutjanus sp. in Saddah Gohoge grits, but the water content decreased due to the use of the same volume of water and the composition of Saddah Gohoge. Hedonic quality organoleptic appearance is not dull, the texture is slightly smooth and slightly thick, the color is slightly yellowish, the flavour is slightly pungent, flavour of corn, the taste is corn. The results of the hedonic organoleptic test of the panelists gave a favorable response for all criteria of appearance, texture, color, aroma, and taste.